Menciptakan Lingkungan Sehat untuk Meningkatkan Kesehatan Warga di Desa Sambiroto RW 7 Kelurahan Sambiroto - Iqbal Hidayatsyah Noor; Grasio Barlia; Fariska Arlinda Putri; Danusiri Danusiri; Mohammad Ridwan (Pusat Riset dan Inovasi Nasional, 2025)
Successful development encompasses various aspects of community life and cannot be separated from progress in the health sector. Health is one of the key indicators in determining the quality of life of a population. Therefore, attention to health—especially for vulnerable groups such as the elderly—is of great importance. Regular health check-ups serve as a preventive measure to help the community detect illnesses early and encourage individuals to take an active role in maintaining their own health. Several types of examinations are commonly provided free of charge during community service activities, including blood pressure checks, random blood glucose tests, uric acid level tests, and cholesterol level screenings. These health checks are especially beneficial for the elderly, as they help monitor overall health conditions and enable early management of diseases to prevent further complications. In this activity, a total of 40 elderly individuals voluntarily participated in the health screening. The methods used included health education sessions and direct examinations of blood pressure, uric acid levels, and random blood glucose levels. The counseling was delivered using simple and clear language, and it included a question-and-answer session to help participants better understand the information provided. The results of the examinations showed that some of the elderly participants had high blood pressure and elevated blood glucose levels, which led to recommendations for follow-up visits to nearby healthcare facilities. Through this health screening initiative, the overall health quality of the elderly participants improved, and their awareness of the importance of early detection increased. This activity is expected to motivate the broader community to pay more attention to their health and to undergo regular health check-ups. By taking a proactive role in managing their well-being, individuals can reduce the risk of serious complications in the future and contribute to the creation of a healthier society overall.